FREE WEIGHT TRAINING IN THE METHOD OF COMPENSATORY ACCELERATION AND ITS IMPACT ON KINETIC SPEED AND ACCURACY OF HANDBALL SHOOTING FOR YOUNG PEOPLE - AMER ADNAN MEZHER (European Journal of Humanities and Educational Advancements, 2023)
Using free weight exercises with compensatory acceleration for handball players aims to develop overall muscle strength. This is achieved by increasing the players’ capacity to exert high levels of strength in the shortest possible time. Failure to apply the ladder to the training mechanism with free weights depends on coaches assessing the force exerted by the players towards these resistances, without considering the degree of acceleration at which the lifted weight moves during the initial pull. This, in turn, hinders the impact of the weight on muscle groups in the final part of the movement, making it difficult to generate new strength. The researcher conducted an experimental study using a single-group experimental design suitable for the research’s nature, involving 10 young handball players from the Al-Najaf Sports Club to execute the study’s goals